Effectively Enhanced Photocatalytic Performance of BP/BiOBr 2D/2D Z-Scheme Heterojunction - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Jinming Zhu; Zuoji Liu; Chaozhong Li; Rong Li; Guangwei Feng; Ke Xu (Molecules, 2025)
Black phosphorus (BP) is a novel two-dimensional (2D) material with remarkable potential for use in environmental remediation and energy conversion. However, the practical application of BP is significantly limited by its low catalytic efficiency and poor structural stability. In this study, a Z-scheme BP/BiOBr 2D/2D heterojunction was fabricated using a simple solution reaction method at room temperature. The BP/BiOBr heterojunction exhibited significantly enhanced photocatalytic performance in the degradation of various organic pollutants and the production of hydrogen under visible light irradiation. This improved activity can be attributed to the efficient separation of photogenerated charges and the extended lifetime of charge carriers within the heterojunction. The durability and structural stability of the BiP-10 heterojunction were demonstrated through cycling tests, which maintained high photocatalytic efficiency over multiple uses. This study presents a promising approach to the development of BP-based photocatalytic materials for sustainable environmental and energy applications.